(untitled) (Fiep Bulletin - online, 2014)
This present study aimed to verify through the accounts how the School Physical Education was characterized in the 1960s and 1970s from the participators from the Elderly Acquaintance Group in Marechal Cândido Rondon - Pr. Thus, this study has been characterized as a Qualitative Survey in the modality Study of Case. 16 individuals have taken part in the study, from them eight from the Paz e Amor Group (Peace and Love Group) and eight from the Amizade Group (Friendship Group), with similar proportions for the male and female gender. In order to verify the Physical Education History in the life of the participators in the survey, a semi-structured interview has been carried out. After the interview analysis, is has been concluded that the Physical Education in 1950s and 1960s was not inserted as effective curricular component in all the schools, in addition to this, it has also been verified through the individual’s speech that there were not a school Physical Education with specific objectives related to a knowledge body as we know these days. The activities were developed through empirical methods, without scientific foundations, disentailed from an educational practice and with a predominantly militarist characteristic.